Altered microsatellites in incomplete-type intestinal metaplasia adjacent to primary gastric cancers. Issue 10 (October 1997) - Hamamoto, T; Yokozaki, H; Semba, S; Yasui, W; Yunotani, S; Miyazaki, K; Tahara, E
Abstract : AIM: To investigate the presence of genetic instability in precancerous lesions of the stomach. METHODS: Fifteen cases of sporadic gastric cancers with a background of intestinal metaplasia were studied by microsatellite assay at nine loci. Altered metaplastic mucosa was microdissected, reconstructed topographically, and examined immunohistochemically with an anti-p53 antibody, comparing its positive area with foci of microsatellite instability in each individual. RESULTS: Alterations at one or more loci were observed in seven of 15 cancers (46.7%) and four of 15 intestinal metaplasias (26.7%). Two cases of replication error positive phenotype had no microsatellite alterations in their metaplastic mucosa. All the microsatellite alterations in the metaplastic mucosa were restricted to incomplete-type intestinal metaplasia around the respective cancers. Moreover, in one case, an identical pattern of microsatellite alteration was detected in the cancer tissue and in the adjacent metaplastic mucosa, suggesting the sequential development of gastric cancer from intestinal metaplasia. Frequent alteration was found at the locus D1S191 (1q), indicating that this locus might be altered early in the development of intestinal-type gastric cancer. No significant association between microsatellite instability and p53 immunoreactivity was observed in the cases examined. CONCLUSION: These results indicate that microsatellite instability may be an early event in stomach carcinogenesis, especially in intestinal-type cancers.